(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2016)
Malignant Fibrous Histiocytoma (MFH) is a soft tissue sarcoma usually involving limbs and retroperitoneum. MFH of the anterior abdominal wall is rare with a high recurrence rate. Though wide surgical excision is the mainstay of treatment, it creates large abdominal wall defects that need reconstruction. The addition of chemotherapy and radiotherapy optimize the chances of survival and cure. We report a case of twice recurrent pleomorphic spindle cell sarcoma of the anterior abdominal wall in pregnancy, with adverse maternal and fetal outcome.